LncRNA MIR4435‐2HG promoted clear cell renal cell carcinoma malignant progression via miR‐513a‐5p/KLF6 axis. Issue 17 (30th July 2020) - Zhu, Kai; Miao, Chenkui; Tian, Ye; Qin, Zhiqiang; Xue, Jianxin; Xia, Jiadong; Zhu, Shenhao; Xu, Aiming; Yang, Jie; Wang, Zengjun
Abstract: Long non‐coding RNAs (lncRNAs) take various biological effects in clear cell renal cell carcinoma (ccRCC) mostly through sponging with microRNAs (miRNAs). lncRNA MIR4435‐2HG is found to promote tumour progression in gastric cancer, glioblastoma and hepatocellular carcinoma. However, the role of lncRNA MIR4435‐2HG in ccRCC progression remains unknown. The purpose of this research was to investigate the potential molecular mechanism of lncRNA MIR4435‐2HG regarding the regulation of ccRCC initiation and progression. In this study, we found the up‐regulation of MIR4435‐2HG in ccRCC tissues and cell lines. Functionally, overexpression of MIR4435‐2HG promoted the proliferation as well as the metastasis in ccRCC cell lines, whereas knockdown of MIR4435‐2HG inhibited the above changes. Then, bioinformatic analysis and luciferase reporter assays confirmed the negative regulation effect of MIR4435‐2HG on miR‐513a‐5p. And further investigations showed that KLF6, which collected from the intersection of databases, was the potential conjugated mRNAs of miR‐513a‐5p. Finally, the rescue experiments revealed the relation among MIR4435‐2HG and KLF6, which showed that KLF6 could reverse the promoting effect of MIR4435‐2HG on ccRCC in vitro and in vivo. Therefore, our findings provided insight into the mechanisms of MIR4435‐2HG in ccRCC and revealed an alternative target for the clinical diagnosis and treatment of ccRCC.